Identification and structure–activity relationship of purine derivatives as novel MTH1 inhibitors. (7th December 2016) - Kumar, Ashutosh; Kawamura, Tatsuro; Kawatani, Makoto; Osada, Hiroyuki; Zhang, Kam Y. J.
Abstract : The human mutT homolog‐1 (MTH1) protein prevents the incorporation of oxidized nucleotides such as 2‐OH‐dATP and 8‐oxo‐dGTP during DNA replication by hydrolyzing them into their corresponding monophosphates. It was found previously that cancer cells could tolerate oxidative stress due to this enzymatic activity of MTH1 and its inhibition could be a promising approach to treat several types of cancer. This finding has been challenged recently with increasing line of evidence suggesting that the cancer cell‐killing effects of MTH1 inhibitors may be related to their engagement of off‐targets. We have previously reported a few purine‐based MTH1 inhibitors that enabled us to elucidate the dispensability of MTH1 in cancer cell survival. Here, we provide a detailed process of the identification of purine‐based MTH1 inhibitors. Several new compounds with potency in the submicromolar range are disclosed. Furthermore, the structure–activity relationship and associated binding mode prediction using molecular docking have provided insights for the development of highly potent MTH1 inhibitors. Abstract : A series of compounds belonging to the purine scaffold have been screened for MTH1 inhibitory activity, and several new inhibitors with potency in the submicromolar range have been discovered. The structure activity relationship of these compounds has been analyzed, and their associated binding modes to MTH1 have been predicted using molecular docking. These studies have provided insights for the development of highly potent MTH1 inhibitors.